2010
DOI: 10.1086/bblv218n3p237
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Patterns of Zoochlorellae and Zooxanthellae Hosted by Two Pacific Northeast Anemones, Anthopleura elegantissima and A. xanthogrammica

Abstract: This study investigated patterns in the relative abundance of two photosynthetic algal symbionts, zoochlorellae (ZC) and zooxanthellae (ZX), hosted by two temperate anemones, Anthopleura elegantissima and A. xanthogrammica. Previous studies have documented varying proportions of each symbiont along environmental gradients, presumably determined by their respective physiological capabilities. To test for differences in the algal type between the two host species, we sampled anemone tissues (tentacle or tentacle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…E. marina occurs much higher in the intertidal zone and approximately 6u farther south in A. xanthogrammica than in A. elegantissima (Bates 2000;Secord and Augustine 2000). These contrasting distribution patterns do not appear to be related to differences in habitat or the relative size of the two anemone species (Bates et al 2010), and suggest that symbiont physiology cannot entirely account for symbiont zonation and biogeography. Nevertheless, the physiological hardiness of high-latitude symbionts is clear (Muller-Parker et al 2007).…”
Section: Discussionmentioning
confidence: 91%
“…E. marina occurs much higher in the intertidal zone and approximately 6u farther south in A. xanthogrammica than in A. elegantissima (Bates 2000;Secord and Augustine 2000). These contrasting distribution patterns do not appear to be related to differences in habitat or the relative size of the two anemone species (Bates et al 2010), and suggest that symbiont physiology cannot entirely account for symbiont zonation and biogeography. Nevertheless, the physiological hardiness of high-latitude symbionts is clear (Muller-Parker et al 2007).…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, where E. marina co-occurs in the two host species, it is typically only hosted by A. elegantissima in the low intertidal zone, whereas in A. xanthogrammica it is hosted much further up the shore (Secord and Augustine, 2000). Furthermore, E. marina is more prevalent in A. xanthogrammica even among similar-sized individuals of the two host species living adjacent to each other in the same habitat (Bates et al, 2010). The symbiotic dinoflagellate S. muscatinei, meanwhile, is considerably more prevalent in A. elegantissima than in A. xanthogrammica.…”
Section: Al 2005) Bhagooli and Hidakamentioning
confidence: 99%
“…Bates et al (2010) compared A. xan thogrammica and A. elegantissima of similar sizes that co-occurred in tidepools and rock crevices and found that more than 95% of A. elegantissima individuals contained primarily zooxanthellae, while 55% of A. xanthogrammica individuals contained primarily zoochlorellae. It is possible that the relatively high nutritional contributions of zoochlorellae 91 Mar Ecol Prog Ser 453: 79-94, 2012 observed in the present study are typical for the A. xanthogrammica symbiosis.…”
Section: Discussionmentioning
confidence: 99%